1997
DOI: 10.1002/(sici)1099-1344(199705)39:5<409::aid-jlcr989>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective deuterium labeling of 1,4-disubstituted-1,2,3,6-tetrahydropyridines

Abstract: Reactions leading to the regioselective deuterium labeling of the 1,4‐disubstituted‐1,2,3,6‐tetrahydropyridine system are presented. Three synthetic approaches were explored: Base catalyzed proton‐deuteron exchange, reductive deuteration, and ring synthesis using deuterated agents. The methods were applied to various pyridinium salts, pyridones, and piperidones. The syntheses of several new labeled compounds are described and a brief review of the relevant literature is included. © 1997 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Deuterium oxide, NaBD 4 , perdeuteropyridine, and all other reagents were supplied by Aldrich Chemical Company (St. Louis, MO, USA). The syntheses of 1 and deuterium‐labeled analogs of 1 were based on modified procedures developed for the synthesis of substituted 1,2,3,6‐tetrahydropyridines 11–16. A general synthetic scheme is outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Deuterium oxide, NaBD 4 , perdeuteropyridine, and all other reagents were supplied by Aldrich Chemical Company (St. Louis, MO, USA). The syntheses of 1 and deuterium‐labeled analogs of 1 were based on modified procedures developed for the synthesis of substituted 1,2,3,6‐tetrahydropyridines 11–16. A general synthetic scheme is outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Substitution of NaBD 4 (229 mg, 5.46 mmol) for NaBH 4 in the synthesis of 1 provided 1‐d 2 (269 mg, 78.1%) following an adapted method of Mabic et al 16 . 1 H‐NMR (CDCl 3 ): δ (ppm) = 7.4–7.2 (m, 5H, ArH); 5.9–5.8 (m, 1H, vinylic H); 5.8–5.7 (m, 1H, vinylic H); 3.2–3.0 (m, 1H, C‐6 H); 3.0–2.9 (m, 2H, N‐CH 2 ); 2.8–2.6 (m, 3H, C‐2 H and CH 2 Ar); 2.3–2.2 (bs, 2H, C‐3 H).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Closer examination of the UV scans of incubation mixtures containing 26 or 27 and MAO-B revealed that the spectra corresponding to the dihydropyridinium metabolites 46 and 47 (Scheme ) shifted with time from a λ max of 360 nm toward a λ max of 325 nm, suggesting their further oxidation to the pyridinium species 34 and 36 , respectively. In the absence of pure synthetic standards, the possible formation of pyridinium products in these reactions was examined by GC−EIMS following treatment of the incubation mixtures with NaBD 4 . The detection of 26- 2,6 - d 2 confirmed the suspected formation of the benzimidazolylpyridinium species 34 .…”
Section: Resultsmentioning
confidence: 99%